2014
DOI: 10.1128/iai.00721-13
|View full text |Cite
|
Sign up to set email alerts
|

Limited Role of Nuclear Receptor Nur77 in Escherichia coli-Induced Peritonitis

Abstract: c Nuclear receptor Nur77 (NR4A1, TR3, or NGFI-B) has been shown to play an anti-inflammatory role in macrophages, which have a crucial function in defense against peritonitis. The function of Nur77 in Escherichia coli-induced peritoneal sepsis has not yet been investigated. Wild-type and Nur77-knockout mice were inoculated with E. coli, and bacterial outgrowth, cell recruitment, cytokine profiles, and tissue damage were investigated. We found only a minor transient decrease in bacterial loads in lung and liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
2
16
1
Order By: Relevance
“…Nevertheless, our data suggest that chronic overexpression (and thus, overactivation) of HOXD10, and also lack of HOXD10, do have a clear effect on LEC junctional integrity and permeability. In this context, it is interesting that NR4A1, the immediate early transcription factor dependent on HOXD10, has been found to regulate permeability in blood vascular endothelial cells, by reducing expression of VE-cadherin and claudin-5, and by inducing NOS3 (also known as e-NOS) (Hamers et al, 2014;Zhao et al, 2011). In line with those findings, we found similar changes in gene expression in LECs overexpressing HOXD10, suggesting that HOXD10 could regulate LECs permeability through NR4A1.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, our data suggest that chronic overexpression (and thus, overactivation) of HOXD10, and also lack of HOXD10, do have a clear effect on LEC junctional integrity and permeability. In this context, it is interesting that NR4A1, the immediate early transcription factor dependent on HOXD10, has been found to regulate permeability in blood vascular endothelial cells, by reducing expression of VE-cadherin and claudin-5, and by inducing NOS3 (also known as e-NOS) (Hamers et al, 2014;Zhao et al, 2011). In line with those findings, we found similar changes in gene expression in LECs overexpressing HOXD10, suggesting that HOXD10 could regulate LECs permeability through NR4A1.…”
Section: Discussionsupporting
confidence: 79%
“…macrophage NF-kB signaling 65 . Other studies have indicated that Nr4a1 does not alter immune cell responses but instead antagonizes endothelial responses to inflammation 66 . In regards to the CNS, Nr4a1 has been implicated in adult brain injury to promote neuroinflammation and cell death 17,18 .…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, subsequent research has failed to replicate these findings, either in bone--marrow-derived macrophages or in vivo [55]. In addition, Nr4a1 -/-mice have a normal immune response in a model of Escherichia coli peritonitis, with no difference in bacterial load, cytokine profile or leukocyte numbers [56]. NR4A1 does not solely exert its effects in myeloid cells, and there is little consideration in this patent or the literature of the consequences of its systemic activation or inhibition.…”
Section: Monocyte/macrophage Modification In Vivomentioning
confidence: 83%